Pengaruh Pelayanan Informasi Obat terhadap Kepuasan Pasien di Apotek X Kabupaten Bangkalan - Dian Parwati; Yohana Febriani Putri Peu Patty (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Pharmacy is a pharmaceutical service facility where pharmaceutical practice is carried out by pharmacists. Pharmacists who work in the field or specialization of Community Pharmacy are health workers who are most easily encountered by the public. Therefore, optimizing pharmaceutical practice by pharmacists to implement pharmaceutical care in pharmacies has an important role and must be continuously improved. One of the benchmarks for the success of pharmaceutical care is clear drug information services that create patient satisfaction. The main tasks of pharmacists in pharmacies are divided into two main parts, namely drug management and pharmaceutical services. Medicine is now not only product-oriented but also patient-oriented. So that the assessment of drug information services is also part of customer satisfaction. The purpose of this study was to determine the effect of drug information services on patient satisfaction at Pharmacy X, Bangkalan Regency. This research method was conducted descriptively with a cross-sectional method. Sample selection was carried out using purposive sampling involving 100 respondents who met the inclusion criteria. Data collection was carried out by interview method. The results of this study on the Responsiveness variable, 90% stated that they were satisfied, while 10% stated that they were not satisfied. For the empathy variable, 96% stated that they were satisfied, while 4% stated that they were dissatisfied. These results indicate that most respondents are satisfied.